2022
DOI: 10.3390/ijerph19052979
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Emergency Remote Teaching on College Students Amid COVID-19 in the UAE

Abstract: With the aim of appraising the impact of Emergency Remote Teaching (ERT) amidst the COVID-19 pandemic on college students, an online survey was conducted in December 2020 on a total of 588 undergraduate students at the American University of Sharjah in the United Arab Emirates. The purpose of the study was to probe into the perceptions of college students regarding their learning process and its influence on their mental health with the abrupt transition from face-to-face classes to ERT in the Spring 2020 seme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 74 publications
(81 reference statements)
1
15
0
Order By: Relevance
“…Other issues frequently addressed in the literature on ERT and the pandemic include the impacts of ERT on students and teachers (Day et al, 2021;El-Sakran et al, 2022;Jelinska & Paradowski, 2021;Kamal et al, 2021;Purushotham & Swathi, 2020), factors affecting the quality of e-learning in the COVID pandemic (Elumalai et al, 2020;Kawasaki et al, 2021), the relationship between ERT and academic performance (Nazempour et al, 2022;Advanced Education ISNN 2409-3351 (Print) ISNN 2410-8286 (Online) Oraif & Elyas, 2021), online formative assessment (Said Pace, 2020;Zou et al, 2021), interaction in online teaching (Yang & Lin, 2020), ERT and the role of teachers' online community of practice (Ulla & Perales, 2021), ERT and parents' involvement (Safriyani et al, 2022), and teaching practicum of pre-service teachers in DE (Koşar, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other issues frequently addressed in the literature on ERT and the pandemic include the impacts of ERT on students and teachers (Day et al, 2021;El-Sakran et al, 2022;Jelinska & Paradowski, 2021;Kamal et al, 2021;Purushotham & Swathi, 2020), factors affecting the quality of e-learning in the COVID pandemic (Elumalai et al, 2020;Kawasaki et al, 2021), the relationship between ERT and academic performance (Nazempour et al, 2022;Advanced Education ISNN 2409-3351 (Print) ISNN 2410-8286 (Online) Oraif & Elyas, 2021), online formative assessment (Said Pace, 2020;Zou et al, 2021), interaction in online teaching (Yang & Lin, 2020), ERT and the role of teachers' online community of practice (Ulla & Perales, 2021), ERT and parents' involvement (Safriyani et al, 2022), and teaching practicum of pre-service teachers in DE (Koşar, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Convenience, time effectiveness and improved participation were the most frequently identified positive aspects, while problems with Internet connectivity, access to ICTs, and insufficient levels of university support were the main challenges. In another study of the experiences of UAE university students, El-Sakran et al [23] found that certain groups of students were significantly more likely to experience heightened stress during emergency remote learning including female students.…”
Section: Arab University Students' Experiences Of Emergency Remote Le...mentioning
confidence: 99%
“…In December 2020, the impact of teaching online on a total of 588 students from the American University of Sharjah in the United Arab Emirates was analyzed. The psychological sufferings of the students were mainly caused by the quality of the courses, the academic performance, and the preparation for future studies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%